2018
DOI: 10.1523/jneurosci.3006-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Unattended Stimuli Depends on the Phase of Prestimulus Neural Oscillations

Abstract: Neural oscillations appear important for perception and attention processes because stimulus detection is dependent upon the phase of 7-11 Hz oscillations before stimulus onset. Previous work has examined stimulus detection at attended locations, but it is unknown whether unattended locations are also subject to phasic modulation by ongoing oscillatory activity, as would be predicted by theories proposing a role for neural oscillations in organizing general neural processing. Here, we recorded brain activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 51 publications
11
71
0
1
Order By: Relevance
“…what phase) our neural oscillations happen to be. As reported by a number of recent studies (Busch et al 2009;Mathewson et al 2009;Sherman et al 2016;Harris et al 2018), our visual detection thresholds notably vary with alpha-band phase. That is, we are able to detect weaker visual stimuli when the stimulus is presented in phase with alpha oscillations (i.e.…”
Section: The Challenge From Neural Phasesupporting
confidence: 81%
“…what phase) our neural oscillations happen to be. As reported by a number of recent studies (Busch et al 2009;Mathewson et al 2009;Sherman et al 2016;Harris et al 2018), our visual detection thresholds notably vary with alpha-band phase. That is, we are able to detect weaker visual stimuli when the stimulus is presented in phase with alpha oscillations (i.e.…”
Section: The Challenge From Neural Phasesupporting
confidence: 81%
“…Based on our investigation of reaction times, phase coherence is correlated with subsequent response times of the subject, as a signature of perception efficacy. Similarly, Harris et al reported that detection of targets depends upon the low frequency phase (in both attended and unattended locations) 67 . Furthermore, Busch and VanRullen reported that the visual detection threshold is periodic and strongly correlated with the pre-stimulus phase of EEG signals 42 .…”
Section: Discussionmentioning
confidence: 93%
“…Based on our investigation of reaction times, phase coherence determines subsequent response times of the subject, as a signature of perception efficacy. Similarly, Harris et al reported that detection of targets depends upon the low frequency phase (in both attended and unattended locations) (Harris et al, 2018). Also, Fiebelkorn et al documented that the fronto-parietal network’s low frequency fluctuations coordinates the attentional spatial sampling (Fiebelkorn et al, 2018).…”
Section: Discussionmentioning
confidence: 95%